Discrete emotions shape gender role attitudes: exploring the impact of gender-stereotyped Douyin urban romantic short dramas on Chinese youth - Lou, Shijun; Adzharuddin, Nor Azura; Syed Zainudin, Sharifah Sofiah; Omar, Siti Zobidah (Redfame Publishing, 2025)
This research investigates how gender stereotypes in Douyin urban romance short dramas influence Chinese youth's gender role attitudes through discrete emotions. Drawing on cultivation theory and the feelings-as-information theory, the study employed a pretest-posttest control group experimental design with 320 college students (160 males, 160 females). Findings revealed that male stereotypes primarily evoked joy and sadness emotions, strengthening identification with traditional male roles; female stereotypes mainly triggered negative emotions, particularly disgust and fear, which promoted acceptance of traditional female roles. Notably, sadness emotions did not prompt males to critically reflect on gender stereotypes, nor did fear guide females to question social gender roles. Short videos construct cognitive imbalance through differentiated emotional induction: placing males in positive emotional atmospheres and females in negative emotional environments, forming an emotional fixation phenomenon that reinforces gender bias. The research also found that young males were more easily assimilated by this content. This gender-based emotional polarization mechanism provides a new explanatory perspective for understanding the increasing gender antagonism and communication barriers in contemporary Chinese social media environments, offering important implications for platform content regulation and youth media literacy education.